Pengaruh Current Ratio, Return On Asset, dan Debt to Equity Ratio Terhadap Price to Book Value Pada PT Astra Agro Lestari Tbk Periode Tahun 2012-2022 - Nadilla Damayanti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The This study aims to examine the effect of the Current Ratio, Return On Assets, and Debt to Equity Ratio on the Price to Book Value of PT Astra Agro Lestari Tbk for the period 2012-2022 using a quantitative method. The population of this study consists of financial reports from PT Astra Agro Lestari Tbk for the specified period. The analysis results show a coefficient of determination (R²) of 0.735, meaning that 73.5% of the variation in Price to Book Value can be explained collectively by these three variables. Conversely, 26.5% of the variation in Price to Book Value cannot be explained by this model, indicating the presence of other influencing factors. The partial t-test results show that the Current Ratio does not have a significant effect on the Price to Book Value with a t-value of 0.552 (below the t-table value of 2.36462) and a significance value of 0.598 (greater than 0.05), leading to the rejection of H1. Similarly, Return On Assets also does not have a significant effect with a t-value of 2.092 (below the t-table value of 2.36462) and a significance value of 0.075 (greater than 0.05), leading to the rejection of H2. Debt to Equity Ratio also does not show a significant effect with a t-value of 1.211 (below the t-table value of 2.36462) and a significance value of 0.265 (greater than 0.05), leading to the rejection of H3. However, when tested simultaneously, these three variables have a significant effect on the Price to Book Value, as evidenced by an F-value of 6.456 (greater than the F-table value of 4.35) and a significance level of 0.020 (less than 0.05), leading to the acceptance of H4